Adaptação transcultural e análise das propriedades do Measure of Intermittent and Constant Osteoarthritis Pain (ICOAP) joelho para o português do Brasil em indivíduos com osteoartrite do joelho - Santana, Gabriela Nascimento de (2023)
Objective: To carry out the translation, cross-cultural adaptation and validation into Brazilian Portuguese of the Intermittent and Constant Osteoarthritis Pain (ICOAP) in individuals with knee OA. Materials and Methods: This is a methodological study, carried out in the integrated health outpatient clinics of the Universidade Nove de Julho, basic health units , in private clinics and offices, with the procedures reported here being approved by the Research Ethics Committee with registration under CAAE No. 32671720.7.3001.5087 . The process of translation and cross-cultural adaptation of the ICOAP knee into Brazilian Portuguese followed international criteria , with the following stages being carried out : translation , synthesis of translations , back-translation , analysis by a committee ̂ of specialists, test of the version pre ́-final and definition of the final version . The psychometric properties evaluated were: structural validity through factor analysis ( exploratory and confirmatory ); test-retest reliability using the intraclass correlation coefficient (ICC); internal consistency through Cronbach 's alpha ; construct validity through correlations between ICOAP and numeric pain scale (END), International Knee Documentation Committee (IKDC), Medical Outcome Study 36 – Item Short- Form Health Survey (SF-36). Results: Fifty individuals diagnosed with knee osteoarthritis were included for validity analyses, and a subsample of 53 individuals was used for test-retest reliability. For structural validity, the original structure of the ICOAP Portuguese knee in Brazil presented all the appropriate fit indices : chi -square/GL = 1.48; CFI = 1.00; TLI = 1.00; RMSEA (90% CI) = 0.068 (0.027 to 0.102); SRMR = 0.045. In the reliability analysis , it presents excellent values regarding test-retest reliability and internal consistency , with an ICC value = 0.95 and Cronbach 's alpha = 0.945 for the constant pain domain . And ICC = 0.92 and Cronbach 's alpha = 0.920 for the intermittent pain domain . Regarding the validity of the construct, there was greater emphasis on the constant pain domain with correlations greater than 0.50 between the ICOAP knee and IKDC , SF-36, and the NS. Conclusion : The Brazilian version of the ICOAP Knee with two domains and 12 items has psychometric properties acceptable , with support for its use in individuals with knee osteoarthritis.